1998
DOI: 10.1046/j.1365-3148.1998.00173.x
|View full text |Cite
|
Sign up to set email alerts
|

Rh phenotype prediction by DNA typing and its application to practice

Abstract: The complexity of the RHD and RHCE genes, which is the greatest of all blood group systems, confounds analysis at the molecular level. RH DNA typing was introduced in 1993 and has been applied to prenatal testing. PCR-SSP analysis covering multiple polymorphisms was recently introduced for the screening and initial characterization of partial D. Our objective is to summarize the accrued knowledge relevant to the approaches to Rh phenotype prediction by DNA typing, their possible applications beyond research la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
59
0
3

Year Published

2001
2001
2013
2013

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 73 publications
(64 citation statements)
references
References 134 publications
2
59
0
3
Order By: Relevance
“…In a study with African blacks, 74% of Rhcc individuals contained a cytosine at nucleotide 48 [14]. In this study we observed a 7.2% (4/55) false-heterozygous rate when genotyping serologically typed Rhcc Caucasian individuals, which is consistent with the previous reports [13,14,18,29]. However, a 56.3% (45/80) false-heterozygous rate was observed when genotyping serologically typed Rhcc African American individuals, which drastically decreases the utility of this polymorphic position for RHC genotyping within this ethnic group.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In a study with African blacks, 74% of Rhcc individuals contained a cytosine at nucleotide 48 [14]. In this study we observed a 7.2% (4/55) false-heterozygous rate when genotyping serologically typed Rhcc Caucasian individuals, which is consistent with the previous reports [13,14,18,29]. However, a 56.3% (45/80) false-heterozygous rate was observed when genotyping serologically typed Rhcc African American individuals, which drastically decreases the utility of this polymorphic position for RHC genotyping within this ethnic group.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, this locus can be used with reasonable confidence to establish the fetal absence of the RHC allele in Rhcc mothers sensitized to RhC with the recognition that there is the possibility of a falseheterozygous genotyping of the fetus. A unique 109-bp insertion within intron 2 of the RHCE gene has completely correlated with RhC serology among more than 600 individuals [18,19]. In this study, primers were developed which flank the intron 2 insertion point and detection of the insertion was correlated with RhC serology among Caucasians and African Americans.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The difference between Rhc and RhC/D is enclosed in a 4247 basepair stretch of near nucleotide identity between the two genes making specific DNA detection of the RHC allele by simple PCR virtually impossible in RHD positive individuals. 3,4 Our method may also be useful if there is concern about microchimerism after bone marrow or organ transplant, or after blood transfusion. [14][15][16] As preliminary experiments showed that reticulocytes survive for at least 34 days when stored at 4°C, we wanted to investigate the maturation pattern of reticulocytes under different temperatures and oxygen tensions.…”
Section: Resultsmentioning
confidence: 99%
“…The approach also facilitates the genotyping of RHC which has been difficult in RhD-positive subjects. 3,4 As reticulocytes are known to have a long lifespan at 4°C we studied their in vitro maturation time to see if transfused reticulocytes might interfere with our method. No interference was observed as reticulocyte maturation is rapid at body temperature.…”
Section: Introductionmentioning
confidence: 99%